Reliability of 20kV Distribution Network Power Systems Using the Reliability Network Equivalent Approach (RNEA) Method - Azzahra Rohali; agung trihasto; deria pravitasa (Program Studi Teknik Elektro Universitas Khairun, 2026)
The reliability of the electrical power distribution system is a major factor in ensuring continous power supply to customers. Reliability issues often arise due to the high frequency of disturbances and long recovery times in radial configuration networks. The method used in this study, the Reliability Network Equivalent Approach (RNEA), is used to calculate key reliability parameters, including failure rate (λ), annual unavailability (U), and two key indices, namely the System Average Interruption Duration Index (SAIDI) and the System Average Interruption Frequency Index (SAIFI). The outage data used was from 2024, which reflects the network conditions after the implementation of an automatic protection system and modernization based maintenance. The analysis results show a SAIDI value of 3.932 hours/customer/year and a SAIFI of 2.18 times/customer/year. These values indicate that the SGN02 feeder system has met the national standard SPLN 68-2:1986, but has not yet met the international standard IEEE Std 1366-2003. This difference is due to the length of the line, the radial configuration without backup lines, and the limited number of reclosers and sectionalizers. Overall, this study concludes that system reliability can be improved through the implementation of a semi-loop configuration, the addition of smart reclosers, and the optimization of automation-based protection systems.